A microstructure-based numerical approach for uniaxial fatigue life-based non-uniaxial fatigue life prediction of hypo-eutectoid steels - Jonghoon Shin; Hyunki Kim; Minwoo Kang; Chungan Lee; Seunghyun Hong; Yoon Suk Choi (Journal of Materials Research and Technology)
A numerical methodology was proposed for the microstructure-based prediction of the non-uniaxial fatigue life using the fatigue life prediction model calibrated only by the uniaxial fatigue life data for 44MnSiVS6 hypo-eutectoid steel. The proposed prediction procedure involves the generation of a statistically representative synthetic microstructure, the development of slip system-based fatigue constitutive models for the primary ferrite and pearlite phases constituting the hypo-eutectoid steel, the synthetic microstructure-based finite element simulations for uniaxial, torsional, and in-phase and out-of-phase axial plus torsional fatigue loading conditions using the developed constitutive models, the extraction of the cyclic increment of the fatigue indicator parameters (ΔFIP) from fatigue-simulated microstructures for the local fatigue damage quantification, the calibration of the uniaxial fatigue life prediction model by linking simulated uniaxial ΔFIPs to the uniaxial fatigue life data, and finally the prediction of the non-uniaxial fatigue life (through simulated non-uniaxial ΔFIPs) using the uniaxial fatigue-calibrated life prediction model. Four different fatigue indicator parameters, Smith-Watson-Topper, Brown-Miller, Fatemi-Socie and Garud parameters, were adopted for the ΔFIP quantification, and their non-uniaxial fatigue life predictability was assessed. The fatigue life prediction model, calibrated only by the simulated uniaxial ΔFIPs and the uniaxial fatigue life data, showed the highest non-uniaxial fatigue life predictability, as high as R2 = 0.89, when using the Fatemi-Socie parameter for the quantification of ΔFIP. The spatial distribution of simulated Fatemi-Socie parameter-based ΔFIPs was confirmed to be consistent with the experimentally observed fatigue crack initiation behavior for the hypo-eutectoid steel for all fatigue loading conditions.